Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
[tex]\frac{2\frac{2}{3}-25:12,5 }{(9-6*1\frac{1}{6})*(-2)}=\frac{\frac{8}{3}-\frac{25}{1}:12\frac{1}{2} }{(9-6*\frac{7}{6})*(-2)}=\frac{\frac{8}{3}-\frac{25}{1}:\frac{25}{2} }{(9-7)*(-2)}=\frac{\frac{8}{3}-\frac{25}{1}*\frac{2}{25} }{2*(-2)}=\frac{\frac{8}{3}-2 }{-4}=\\ \frac{\frac{8}{3}-\frac{6}{3} }{-4}=\frac{2}{3}:(-4)}=-\frac{2}{3}*\frac{1}{4}=-\frac{1}{3}*\frac{1}{2}=-\frac{1}{6}[/tex]
[tex]\frac{4\frac{1}{2}*\frac{5}{3}-3\frac{3}{4} }{\frac{5}{9}-\frac{10}{27}*(-\frac{6}{5}) }=\frac{\frac{9}{2}*\frac{5}{3}-\frac{15}{4} }{\frac{5}{9}+\frac{2}{27}*\frac{6}{1}}=\frac{\frac{3*5}{2}-\frac{15}{4} }{\frac{15}{27}+\frac{12}{27} }=\frac{\frac{15}{2}-\frac{15}{4} }{\frac{27}{27} }=\frac{\frac{30}{4}-\frac{15}{4}}{1}=\frac{15}{4}=3\frac{3}{4}[/tex]